2004
DOI: 10.1146/annurev.biochem.72.121801.161455
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase γ, The Mitochondrial Replicase

Abstract: DNA polymerase (pol) gamma is the sole DNA polymerase in animal mitochondria. Biochemical and genetic evidence document a key role for pol gamma in mitochondrial DNA replication, and whereas DNA repair and recombination were thought to be limited or absent in animal mitochondria, both have been demonstrated in recent years. Thus, the mitochondrial replicase is also apparently responsible for the relevant DNA synthetic reactions in these processes. Pol gamma comprises a catalytic core in a heterodimeric complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
318
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(322 citation statements)
references
References 156 publications
3
318
0
1
Order By: Relevance
“…The existence of repair of oxidative damage to mtDNA was established several years ago [151][152][153]. It was also reported that mitochondrial DNA polymerase gamma (Polg) and mtDNA ligase (Lig IIIb), which are involved in mtDNA replication are also functional in mitochondrial BER [154,155]. Lig IIIb is a splice variant of the nuclear Lig IIIa, whereas Polg is unique for the mitochondria [156].…”
Section: Ber In Mitochondriamentioning
confidence: 99%
“…The existence of repair of oxidative damage to mtDNA was established several years ago [151][152][153]. It was also reported that mitochondrial DNA polymerase gamma (Polg) and mtDNA ligase (Lig IIIb), which are involved in mtDNA replication are also functional in mitochondrial BER [154,155]. Lig IIIb is a splice variant of the nuclear Lig IIIa, whereas Polg is unique for the mitochondria [156].…”
Section: Ber In Mitochondriamentioning
confidence: 99%
“…The nuclear gene POLG encodes mitochondrial DNA polymerase gamma 1, which is the only polymerase known to be involved in mtDNA replication and repair in eukaryotes [55]. POLG abnormalities result in mtDNA mutations and/or multiple deletions, and are responsible for the most common cause of inherited mitochondrial diseases in children and adults [56].…”
Section: Polg-related Disordersmentioning
confidence: 99%
“…7,8 Mitochondrial DNA, a 16.5-kb circular double-stranded molecule, is replicated by an assembly of enzymes and proteins consisting of DNA polymerase g (pol g), ssDNAbinding protein, DNA helicase and various accessory proteins and transcription factors. 9 Mitochondrial DNA is prone to mutations, as it is localized near the inner mitochondrial membrane in which reactive oxygen species are generated. In addition, mtDNA lacks histone protection and highly efficient DNA repair mechanisms.…”
mentioning
confidence: 99%